Zehn Jahre in Deutschland - Ji, Xianlin (Universitätsverlag Göttingen, 2009)
The late Chinese scholar Ji Xianlin has influenced the image of Germany for generations of Chinese relevant until today. About his time in Göttingen from 1935 1945 he wrote in the 80's a book in which he draws, in spite of negative experiences during the Nazi dictatorship, a differentiated picture of Germany and the Gottingen science. This led to a sharp increase in the number of Chinese students in Göttingen up to 400 in 2008.